Project NINK Ngipins Inaalagaan para sa Nakangiting Kinabukasan - Grin Movement, Team; Araneta, Francine Nicole M.; Bebita, Valerie Anne N.; Endoma, Vivienne F. (2016.)
Dental caries, also known as cavities or tooth decay, is one of the most prevalent diseases of people worldwide which can start as early as during childhood affecting the primary teeth of children. It is mostly caused by lifestyle-related factors such as poor oral hygiene, lack of dental services, poor habit in brushing teeth and poverty (Ismali et. al. 2007). Iloilo has a high number of dental problems that affect school-aged children. Toothache from dental caries is one of the major causes of absenteeism in elementary schools (Araojo, 2003). The Project NINK aimed to reduce the incidence of dental caries by 80% among school-aged children of Barangay Buenavista Elementary School, Tubungan, Iloilo. A pre-dental check-up, conducted before project implementation found that out of 134 students examined, 125 had dental caries, translating to 9 out of 10 students. For the team to address the existing neglected problem, objectives were set to aid in project implementation. A reliable and self-sustaining core group was formed for the maintenance and sustainability of the project. To address the insufficient knowledge of the children and community members regarding oral health, a series of health lectures were conducted. Topics for the lectures included basics of the teeth, how cavities form, other diseases that may arise from dental caries, and the like. Training courses for the teachers, health workers and midwife were also conducted by the researchers. Incentives were given out during the lectures and proper educational materials were provided as well. A tooth-brushing sink was constructed together with the teachers, parents, community members and the children, to aid in changing the tooth brushing habits of the children. Dental kits were distributed per child and also for families to aid the child in practicing proper oral hygiene. The children?s post-test results showed that the knowledge regarding oral health increased by 27.54% from their pre-test which was statistical significant difference. A statistical significant difference ( t(41)= -8.882, p < 0.0005) was also shown in the post-test and pre-test results of the community members which had an increase of 29%. A post dental check-up was conducted to assess the effect of the project, and it was found out that the mean prevalence rate of dental caries in the temporary teeth of student respondents was successfully decreased by 18.4% from 22.73% to 18.55% (DMFindex) since pre-project, and therefore, effectively reduced the incidence rate by 100% with 0 new cases. For the permanent teeth (DMF index), there was a 19.75% decrease in prevalence rate and a 100% reduction in the incidence rate with no new cases identified.
Research Project - Bachelor of Science in Public Health. University of the Philippines Visayas, Miagao, Iloilo.
Keywords: Dental Caries; Project NINK; Tooth Brushing